Pengaruh Kombinasi Media Tanam dan Cekaman Kekeringan pada Pertumbuhan Vegetatif Tanaman Kedelai (Glycine max L.) - Agung Faisal; M Idris (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of drought stress and planting media combinations on the growth of soybean (Glycine max L.). The research method used was a Randomized Block Design (RBD) consisting of two factors. The first factor was planting media (P0 = 5 kg soil (control)/pot, P1 = 2 kg soil + 2 kg coconut coir (cocopeat) + 1 kg vermicompost/pot, P2 = 2 kg soil + 2 kg rice husk + 1 kg vermicompost/pot, and P3 = 2 kg soil + 1 kg coconut coir (cocopeat) + 1 kg rice husk + 1 kg vermicompost/pot). The second factor was irrigation with four methods (S0 = 100% watering, S1 = 80% watering, S2 = 60% watering, and S3 = 40% watering). The observed parameters included plant height, root length, fresh weight, leaf area, relative growth rate, and net assimilation rate. Data analysis was performed using One-Way ANOVA followed by Duncan’s test at a 5% significance level. The results showed that plant height, leaf area, dry weight, and root length under different planting media indicated that P3 had the highest values, followed by P2. The relative growth rate of soybeans under different planting media showed that P2 was the best, followed by P0, while the net assimilation rate under different planting media showed that P1 had the highest results, followed by P0. The results of plant height, leaf area, dry weight, and root length under drought stress indicated that S0 had the highest values, followed by S1. The relative growth rate of soybeans under drought stress showed that S3 was the best, followed by S2, while the net assimilation rate under drought stress showed that S1 had the highest results. The best treatment combination for plant height, leaf area, root length, and dry weight was P3S0. For relative growth rate, the best combination was P2S3, while for net assimilation rate, the best combination was P1S1. Keywords: Drought Stress, Soybean, Planting Media